UPAYA MENINGKATKAN KEMAMPUAN PRA MENULIS ANAK USIA 5-6 TAHUN MELALUI MEDIA BALOK HURUF DI TK DHARMA WANITA - Husaiwati; Ianatuz Zahro; Trio Suwargono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on efforts to improve the pre-writing skills of children aged 5-6 years through letter blocks media at Dharma Wanita Kindergarten. The problem faced is the low pre-writing skills in children, which is seen from their difficulties in recognizing letters and positioning their fingers when writing. This can hinder children's literacy development in the future. The general objective of this study is to determine children's pre-writing skills. While the specific objectives include; To improve letter recognition in children through letter blocks media and to Create a fun and interactive learning atmosphere. The research method used is Classroom Action Research (CAR), which involves observation and interviews to collect initial data. This research will be conducted in several cycles, where each cycle consists of planning, implementation, observation, and reflection. The use of letter blocks media is expected to make children more active and involved in the learning process. The output of this study is expected to be an increase in children's pre-writing skills, which can be measured through indicators such as the ability to hold writing tools, make meaningful scribbles, and write names in capital letters. In addition, this research is also expected to provide a positive contribution to the development of learning methods in Early Childhood Education (PAUD).